The influence of emphatic /dˁ/ on Modern Standard Arabic vowels: An acoustic analysis - Kalaldeh, Raya; Al-Shdaifat, Abd Allah (Lingua Posnaniensis, 2019)
This study is part of a larger project on the influence of Arabic emphatics /tˁ, dˁ, δˁ, sˁ/ on adjacent Arabic vowels by considering three factors: vowel quality, vowel duration and directionality of emphasis spread. This paper investigates the influence of the voiced alveolar emphatic /dˁ/ on the six Modern Standard Arabic (MSA) monophthongs /ɐ – ɪ – ʊ – a: – i: – u:/ as produced by ten Jordanian speakers. The monophthongs in the adjacency of /dˁ/ are compared to those adjacent to the non-emphatic alveolar voiced stop /d/. Results indicate that in the emphatic context, the vowels are clearly retracted in the vowel space and that the extent of the emphatic influence in ‘preceding’ or ‘following’ contexts is not significantly different.